Who shares? : co-operatives and rural development - Attwood, Donald W.; Baviskar, B. S. (Baburao Shravan), 1931- (Delhi : Oxford University Press, 1988)
Contributed papers on Asia and Africa presented at a symposium held at Montreal, 1983.
Includes bibliographies and index.
Keywords: Cooperative societies -- Asia -- Congresses; Cooperative societies -- Africa -- Congresses